Reliability Evaluation and Failure Behavior Modeling of IMS Considering Functional and Physical Isolation Effects - Chen, Ying; Wang, Ze; Ma, Qichao; Liang, Kun (IEEE/ASME transactions on mechatronics, 2019)
Due to the integration of complex structure and artificial intelligence, the failure behavior of intelligent mechatronic system (IMS) is characterized by functional and physical dependences. In this article, the functional isolation and physical isolation (PI) effects caused by these dependences are studied. We not only analyze the PI effect affecting the failure behaviors of components through failure mechanisms, but also propose a hierarchical method based on binary decision diagram for modeling system failure behavior affected by the PI and functional isolation effect. In the case study, an automatic collision avoidance system as an example of IMS is evaluated for the analysis of failure behavior, which is helpful for more realistic reliability assessment and design optimization.